Pristolepis pentacantha Plamoottil 2015, and Catopra tetracanthus Günther 1862: two junior synonyms of Pristolepis marginata Jerdon 1849 - Prakash, Anjana Preetha; Raghavan, Rajeev; Dahanukar, Neelesh; Anoop, V.k.; Thampy, Dencin Rons; Britz, Ralf; Ali, Anvar (Zootaxa, 2025)
The identities of three species of Pristolepis described from the Western Ghats of India, Pristolepis marginata Jerdon 1849, Catopra tetracanthus Günther 1862, and Pristolepis pentacantha Plamoottil 2015, are resolved. Combined evidence from morphology and mitochondrial COI gene sequences reveals that Pristolepis pentacantha is a junior synonym of P. marginata, and comparison of morpho-meristic data from the two syntypes of C. tetracanthus and topotypic specimens of P. marginata demonstrate that they are conspecific. We show that P. marginata is restricted to tributaries of the east-flowing Cauvery River in the southern Western Ghats.